2016
DOI: 10.15604/ejbm.2016.04.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency Analysis of Singapore Real Estate Investment Trusts

Abstract: Since the REIT industry is relatively new in Singapore, the objective of this research is to examine the operation efficiency among firms in the industry through the method of Data Envelopment Analysis (DEA). In addition, the method of Tobit regression is applied to investigate the impact factors on efficiency. The results are as follows. First, none of 14 firms analyzed performs relatively efficiently based on the average efficiency scores over the sample periods of 2007 to first quarter of 2015. Nevertheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, [24] found that there is no benefits from size for EU REITs, especially after the subprime crisis. In addition, Singapore REITs with midlarge size show insignificant differences on average in efficiency, unlike small size REITs as in [13].…”
Section: Asset Growth and Fund Size Increasementioning
confidence: 87%
“…However, [24] found that there is no benefits from size for EU REITs, especially after the subprime crisis. In addition, Singapore REITs with midlarge size show insignificant differences on average in efficiency, unlike small size REITs as in [13].…”
Section: Asset Growth and Fund Size Increasementioning
confidence: 87%
“…They prove that the overall inefficiency of LRECs is mainly caused by scale efficiency. Hui et al (2016) evaluate the operating efficiency of REITs in Singapore by using the CCR model and apply the tobit regression analysis to explore the influencing factors, which conclude that the return on assets is positively correlated with the operating efficiency of REITs but a negative relationship with the debt ratio. Second, with upgrading the DEA model, more evaluations involve real estate efficiency, mainly including cost efficiency, investment efficiency, sustainable efficiency, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This could probably be because, in the past, most real estate portfolios were generally built on a small scale. Studies covering real estate markets like Germany (Schaefers, 2009), Singapore (Chiang et al , 2016), India (Roy and Kohli, 2016) and Taiwan (Hai-feng and Shuang, 2015) reach different conclusions with regard to capital expenditure (CAPEX) efficiency. For instance, CAPEX efficiency for real estate assets in Europe is moderately high (Hartmann, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These studies focused on the financial instruments related to real estate CAPEX and operational expenditure (OPEX) rather than the operational efficiency of the building assets. Furthermore, these types of empirical analyses are normally ex post analyses, which may only confirm the ex ante investment decisions (Chiang et al , 2016). However, as a result of special property characteristics (heterogeneous), there are a variety of problems in selecting the appropriate asset for investment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation